Effect of green tea marinades on the formation of heterocyclic aromatic amines and sensory quality of pan-fried beef - Quelhas, I (2010)
The effect of a green tea marinade on the formation of heterocyclic aromatic amines (HAs) was examined in pan-fried beef cooked at 180-200 degrees C for 4 min each side. Different marinating times were assayed and unmarinated samples cooked in similar conditions provided reference HAs levels. A green tea marinade catechin rich was prepared taking 1 g of green tea and infusing with 125 ml of boiling tap water during 10 min. Four HAs were quantified in unmarinated and marinated meat samples during 1, 2, 4 and 6 h at 5 degrees C. Compared with the unmarinated samples, marinating in green tea resulted in a significant decrease (p < 0.05) of levels of PhIP and A alpha C. Person correlation indicated that the reduction of the levels of these HAs in meat marinated with the increase of marinating time was significant (respectively, r = -0.799, p < 0.0001; r = -0.631, p < 0.05). No reduction was observed for 4,8-DiMelQx and MelQx. The beef samples were tested for descriptive sensory analysis by two trained sensory panels to evaluate the influence of the green tea marinade in meat organoleptic characteristics. Analysis of results obtained through the r-test, revealed no significant differences (p < 0.05) between control samples and tea marinated samples for all the thirteen attributes evaluated.